GIS mapping-based impact assessment of groundwater contamination by arsenic and other heavy metal contaminants in the Brahmaputra River valley: A water quality assessment study. (10th November 2018) - Nath, B.K.; Chaliha, C.; Bhuyan, B.; Kalita, E.; Baruah, D.C.; Bhagabati, A.K.
Abstract: Groundwater aquifers serve as the primary source of potable water for the vast majority of the population in the Brahmaputra River valley. However, these groundwater reserves form a substantial part of a rapidly weathering alluvial drainage resulting in major contamination by Arsenic (As) and associated heavy metals thereby raising key concern on their safety and sustained usage. The current study entails a comprehensive qualitative analysis of the potable groundwater reserves using a combination of geographical information system (GIS) and geochemical approaches to determine the severity of groundwater contamination by As and other heavy metals in a total of twenty administrative districts of Assam, India. Furthermore, the groundwater solute chemistry and water quality status in the 20 districts of the study area, which encompasses the Brahmaputra River valley, was also assessed to evaluate the sustainability of these potable groundwater reserves. The findings show that the groundwater aquifers present in these districts of the Brahmaputra River valley in Assam are severely contaminated with As with the highest concentration at ∼352.56 ppb being observed in the district of Nagaon. The districts of Tinsukia, Dibrugarh, Sivasagar, Dhemaji, Lakhimpur, Jorhat, Golaghat, Sonitpur, Nagaon, Morigaon, Darrang, Udalguri, Kamrup, Nalbari, and Baksa also showed the presence of elevated levels of dissolved As which on an average exceeded the WHO permissible limit of 10 parts per billion as well as the Bureau of Indian Standards limit of 50 parts per billion. Moreover, notable contamination by other heavy metals including lead, manganese, iron, and zinc exceeding the WHO and BIS prescribed limits were prominent. Also, the groundwater was found to harbour elevated concentrations of ions such as HCO3 −, Ca 2+ and Mg 2+ which impart severe restrictions on to the safety, aesthetics and palatability of these potable water reserves. Furthermore, the dissolved As content was found to exhibit a significant correlation to the elemental contaminants such as iron and manganese suggesting that the reductive dissolution of iron oxyhydroxides may serve as the underlying mechanism for the As enrichment of these groundwater reserves. Additionally, the impact assessment study through the spatial distribution of the groundwater quality index (GWQI) of the areas studied showed that the groundwater reserves in the majority of the administrative districts are unfit for human consumption, without the intervention through requisite water treatment and/or sustainable remediation approaches. These findings indicate the need for serious introspection and reconsiderations on the part of the stakeholders for the sustainable use of these groundwater resources for anthropogenic activities. Highlights: Spatially interpolated distribution maps for groundwater As, heavy metals, pH and depth developed. 16 out of 20 districts surveyed had severe As contamination, highest being ∼352 ppb. 10 new districts found to be affected by As contamination, in the comprehensive study. Modeling of groundwater As showed correlation with Mn and Fe. Groundwater Quality Indexing shows most groundwater reserves unfit for human consumption.